Association between the early or late onset of gestational diabetes mellitus with neonatal adverse outcomes: a retrospective cohort study - Fabiana Vieira Duarte de Souza Reis; Carlos Izaias Sartorão Filho; Luis Sobrevia; Caroline Baldini Prudencio; Bruna Bologna; Luana Favaro Iamundo; Adriely Magyori; Luiz Takano; Raissa Escandiussi Avramidis; Rafael Guilen de Oliveira; Marilza Vieira Cunha Rudge; Angélica Mércia Pascon Barbosa; et al. (Clinical Diabetes and Endocrinology)
Abstract Background The literature has been evolving to standardize gestational diabetes mellitus (GDM) diagnosis and terminology. The significance of timing in diagnosing hyperglycemia during pregnancy is underlined by evidence that women diagnosed at 24 weeks of gestation or earlier are at a higher risk of developing postpartum prediabetes, but its association with adverse outcomes for the newborn is controversial. We aimed to investigate the association between early-onset GDM and adverse outcomes in newborns and neonates, comparing it with the late-onset GDM model. Methods It was a retrospective cohort study conducted at the Perinatal Diabetes Research Center in Assis/SP, affiliated with the Botucatu Medical School-UNESP in Brazil. The group composition was as follows: early-onset participants had fasting glucose levels ≥ 92 mg/dL and < 126 mg/dL before 20 weeks of gestation, while late-onset participants had a negative first-trimester screening and a positive 75g-OGTT at 24–28 weeks. For early-onset GDM, a fasting glucose level of ≥ 92 mg/dL is a recognized threshold associated with an increased risk of adverse pregnancy outcomes, while < 126 mg/dL ensures the exclusion of overt diabetes. The criteria for late-onset GDM, involving a negative initial screening and a positive OGTT at 24–28 weeks, align with the standard diagnostic timeframe when insulin resistance typically peaks due to placental hormone secretion. The maternal baseline characteristics included pre-pregnancy body mass index (BMI; kg/m2) and pregnancy weight gain (kg), calculated as the difference between the final pregnancy weight (36 gestational weeks or more) and pre-pregnancy maternal weight, classified according to the pre-pregnancy BMI. Additionally, the perinatal outcomes evaluated in this study included gestational age (GA) at birth, birth weight (BW) categorized according to GA as adequate, large, or small and Apgar scores at the first and 5th minutes. Results Eight hundred eighty pregnant women were selected, of whom 203 (23.07%) presented GDM and were eligible from December 2016 to December 2021. Based on the timing onset of GDM, 89 (43.8%) were in the early-onset group, and 114 (56.2%) were in the late-onset group. The fasting plasma glucose values in the first trimester were higher in the early-onset group. The 75-g OGTT values were higher in the late-onset group. The final BMI was higher in the early-onset group. Univariate linear regression was performed to determine the relationship between late-onset and maternal and neonatal outcomes; however, no significant relation was detected. Conclusion Pregnant women with early-onset GDM showed a higher BMI during pregnancy, but there was no difference between early and late-onset GDM concerning neonatal adverse outcomes.